Temperature Dependence of Single Molecule Rotation of the Escherichia coli ATP Synthase F(1) Sector Reveals the Importance of γ-β Subunit Interactions in the Catalytic Dwell - Sekiya, Mizuki (American Society for Biochemistry and Molecular Biology, 2009)
The temperature-dependent rotation of F(1)-ATPase γ subunit was observed in V(max) conditions at low viscous drag using a 60-nm gold bead (Nakanishi-Matsui, M., Kashiwagi, S., Hosokawa, H., Cipriano, D. J., Dunn, S. D., Wada, Y., and Futai, M. (2006) J. Biol. Chem. 281, 4126–4131). The Arrhenius slopes of the speed of the individual 120° steps and reciprocal of the pause length between rotation steps were very similar, indicating a flat energy pathway followed by the rotationally coupled catalytic cycle. In contrast, the Arrhenius slope of the reciprocal pause length of the γM23K mutant F(1) was significantly increased, whereas that of the rotation rate was similar to wild type. The effects of the rotor γM23K substitution and the counteracting effects of βE381D mutation in the interacting stator subunits demonstrate that the rotor-stator interactions play critical roles in the utilization of stored elastic energy. The γM23K enzyme must overcome an abrupt activation energy barrier, forcing it onto a less favored pathway that results in uncoupling catalysis from rotation.